Implementasi Penggunaan Kode QR Pada Pemesanan Menu di Cafe Tamulang Banyuwangi - Anggi Dwi Prastya; Nur Ahmadi Indartono (Jurnal Informatika dan Komputer, 2022)
Cafe is one type of business that offers a variety of food and drinks. Every cafe has to serve a large number of orders when implementing a manual ordering process involves ordering errors regarding the menu name and the number of ordered menus. In addition, waiters have a hard time answering customer questions about the status of their orders because they have to go to the kitchen to do it. By implementing the QR Code technology developed in this cafe ordering system, it is hoped that it can manage the flow of the food and beverage ordering process in such a way as to minimize errors. The technology used is a web-based information system by implementing a QR Code on the consumer order menu, where consumers can place orders by scanning through a browser froman Android device as a client then sent through the network to the server and read by the cashier. From this solution a web application was created that is useful for reducing errors in entering orders, maintaining the mobility of waiters because they usemobile devices, food and beverage queues can be managed, besides that it is also possible to manage the provision of information, for example. Order status and menu availability